Some Causes of Organ and Carcass Condemnations in Ostriches Slaughtered at the Only Ostrich Abattoir in Zimbabwe from 1999-2005 - Mukaratirwa, S.; Dzoma, B.M.; Matongo, C.; Nyahuma, M. (International Journal of Poultry Science, 2009)
A retrospective study was conducted to determine the causes of ostrich carcass and organ condemnations in Zimbabwe for the period 1999-2005. Records of meat inspection available at the single ostrich abattoir in Zimbabwe were used in this study. The number of ostriches slaughtered for the whole study period was 55 957. The total number of ostriches slaughtered decreased by 84.8% from 1999-2005. The average age and weight at slaughter were 11 months and 110 kg respectively. The liver was the most frequently condemned organ, mainly due to fatty degeneration, parasitic infestations, cysts, cirrhosis and melanosis. The second most condemned organ was the lung, mainly due to congestion. Traumatic lesions were the main macroscopic findings associated with wing and neck condemnations, while abscessation and pericarditis were mainly associated with gizzard and heart condemnations respectively. Septicaemia was the only cause of whole carcass condemnations and resulted in the condemnation of 0.005% of the slaughtered ostriches. Only a year effect was noted on liver condemnations, which peaked during 2004 and 2005 mainly involving months from May to August. The rest of the condemnations showed neither a month or year effect. No zoonotic causes of condemnations were recorded. Optimal management practices on the farm and observation of proper methods during transportation and slaughtering are some of the ways that may be used to reduce incidences of condemnations.